Effect of digestate and digestate supplemented with biochar on switchgrass growth and chemical composition. (January 2021) - Lee, Moon-Sub; Urgun-Demirtas, Meltem; Shen, Yanwen; Zumpf, Colleen; Anderson, Eric K.; Rayburn, A. Lane; Lee, D.K.
Abstract: Digestate, a by-product of anaerobic digestion, can be an excellent source of nutrients for bioenergy crop production, while biochar, resulting from pyrolyzing biomass, can valorize the nutrients of digestate. The objective of this study was to evaluate the nutritional value of digestate and digestate + biochar for switchgrass production. The greenhouse experiment was conducted to determine the effects of a nitrogen (N) source including 0 N (control), urea (nutrient control), sewage sludge digestate, and sewage sludge digestate + corn stover biochar on switchgrass growth and feedstock composition. Nitrogen sources were found to significantly increase plant weight at the 32-week harvest, with weight ranging from 94.2 to 125.2 g plant −1, depending on the N source, compared to 70.7 g plant −1 from the negative control. Moreover, switchgrass treated with digestate + biochar showed higher plant weight than samples treated only with digestate. Nitrogen application of urea, digestate, and digestate + biochar had positive effects on plant height and total leaf area in the 32-week harvests and chlorophyll content in the 8-week harvests. Feedstock quality traits including hemicellulose, cellulose, and lignin content were not affected by N sources in either the 8 or 32-week harvests with the exception of ash concentration in the 32-week harvests. Our results indicate that digestate and digestate + biochar can be a potential substitute for chemical fertilizer, resulting in increased biomass yield. Highlights: As the demand for alternative energy sources increases, bioenergy crops have gained attention. Even though switchgrass has already been considered a model crop for bioenergy due to its low input and high yield potential, nitrogen (N) management is necessary for sustainable biomass production. Therefore, in this manuscript, we evaluated alternative approaches to chemical fertilizer for supplying N to switchgrass, using digestate and biochar, which may also have environmental benefits. Here are our highlights for this manuscript; 1. Digestate and digestate + biochar had a positive effect on switchgrass biomass yield without harming feedstock quality - Nitrogen sources were found to significantly increase plant weight at the 32-week harvest, with weight ranging from 94.2 to 125.2 g plant −1, depending on the N source, compared to 70.7 g plant −1 from the negative control. - Switchgrass treated with digestate + biochar showed higher plant weight than samples treated only with digestate. - Feedstock quality traits including hemicellulose, cellulose, and lignin content were not affected by N sources 2. Digestate and digestate + biochar could be considered as a potential substitute for chemical fertilizer for switchgrass biomass production